Bringing Up Students in the Healthy Lifestyle Multiplier Students Program, São Paulo, Brazil - Rachel Lima Zanetta, MSW; Moacyr Roberto Cuce Nobre, PhD; Inês Lancarotte, BMedSc (Centers for Disease Control and Prevention, 2008)
Health education practices are central to preventing heart disease. The great challenge remains how to promote the adoption of healthy behaviors that can reduce risk factors for heart disease. In São Paulo, Brazil, the Healthy Lifestyle Multiplier Students program is based on studies that train older students ("multipliers") as peer educators for younger students. These students influence each others' cultural development and psychosocial growth, encourage one another to diversify their social relationships, and transform teaching-learning experiences. This intervention focused on physical activity, healthy diet, and the health effects of cigarette and alcohol consumption.